Improving Approaches to the Formation of Enterprise's Marketing Budgets - Bondarenko, Olena; Kovalchuk, Svitlana; Rodionov, Sergii; Miroshnik, Maria; Kitchenko, Olena; Franchuk, Lesya (My University, 2021)
This article discusses the importance of optimizing advertising budgets for enterprises in the face of fierce competition for the consumer. It highlights the principles that business owners should consider when developing a marketing budget and notes the change in the influence of marketing in the sales funnel. The process of optimization of advertising budgets is presented. Also, the main approaches and methods of forming the marketing budgets of enterprises are highlighted. The method is considered in detail, taking into account the effectiveness of the use of marketing budgets. And recommendations are given on the allocation of budgets within advertising channels, depending on the goals and size of the enterprise.
Keywords: advertising channel; CEO; enterprise; marketing budget